Psychoactive substance use in patients diagnosed with attention-deficit/hyperactivity disorder: an exploratory study - Gniewko Więckiewicz; Iga Stokłosa; Maciej Stokłosa; Włodzimierz Więckiewicz; Piotr Gorczyca; Tomasz M. Gondek (Frontiers in Psychiatry, 2023)
IntroductionAttention-deficit/hyperactivity disorder (ADHD) was originally treated as a neurodevelopmental disorder that occurs mainly in children and tends to diminish or disappear with age, but we now know that symptoms persist into adulthood in over 50% of ADHD patients. Undiagnosed individuals often turn to psychoactive substance to minimize the negative aspects of functioning and improve quality of life.MethodsThe study was conducted online using random sampling through a Facebook group administered by physicians and targeted to patients diagnosed with ADHD. The study was naturalistic and exploratory, therefore no hypothesis was made. 438 correctly completed questionnaires were received. Analysis of the results showed that people with ADHD turn to psychoactive substances relatively frequently.ResultsThe most commonly used stimulants include alcohol, marijuana, 3,4-methylenedioxymethamphetamine (MDMA), amphetamine/methamphetamine, and psilocybin. In the study population, methylphenidate is the most commonly used drug among patients. After treatment with psychostimulants, the majority of respondents note a decrease in symptoms of hyperactivity disorder, especially in male patients.ConclusionIt is necessary to perform proper diagnostics and actively look for ADHD symptoms in patients who tend to use psychoactive substances.